The use of metacognitive strategies and argumentative features in academic writing of tertiary students / Shalini Radha Krishnan - Shalini Radha , Krishnan (2018)
The aim of this study is to provide an insight into the link between metacognitive strategies employed by Malaysian students in learning English as Second Language (ESL) for writing and the argumentative features found in students’ argumentative essays. In addition, this study also aims to explore the various types of metacognitive strategies that are utilized by two different groups of students, namely students who attained high and low scores in their argumentative essay writing and to explore the argumentative features found in the argumentative essays of both groups of students. In order to ascertain the metacognitive strategies employed by students and the argumentative features in argumentative essay writing, this study adopts a mixed method design known as convergent parallel design. The data in this study consisted of quantitative and qualitative data. The Metacognitive Strategies Questionnaire (MSQ) for writing is used to collect data related to the types of metacognitive strategies used by the ESL learners, while Toulmin Model of Argument is used to trace the argumentative features found in their argumentative essays. The findings revealed metacognitive strategies enable students to plan, monitor and evaluate their writing. Therefore, the findings of this study revealed the types of metacognitive strategies used by the students in their writing and how these strategies helped them in their writing. However, the argumentative features produce by the high scorers and also the low scorers in their argumentative essays differ.